Improving carbon management through maximizing hydrolysis and fermentation at water resource recovery facilities - Cecconi, Francesca; Pifer, Leah; Sabba, Fabrizio; Downing, Leon (Frontiers in Environmental Engineering, 2024)
Wastewater treatment plants are transitioning from a sole focus on treatment objectives to integrated resource recovery and upcycling. Effective carbon management is critical for upcycling within a water resource recovery facility (WRRF) to produce energy or other usable products, which involves carbon diversion at primary treatment and waste activated sludge (WAS) from biological treatment processes. Many WRRFs are also driven to meet stringent effluent nutrient discharge targets while minimizing energy usage and chemical addition.Nutrient removal systems still rely on biodegradable organic carbon to support denitrification and enhanced biological phosphorus removal (EBPR). Biological nutrient removal not only requires sufficient organic substrate, but also the right type of bioavailable carbon for optimal utilization.The main objective of this pilot fermentation testing was to evaluate the most effective utilization of the range of organic-carbon rich feedstocks within a WRRF. Preliminary results suggest that a 50-50 blend of primary sludge (PS) and return activated sludge (RAS) fermentation leads to highest volatile fatty acid (VFA) yield. PS fermentation resulted in the minimum nutrients release per unit of volatile suspended solids (VSS), which makes it a best suited for biological nutrients removal WRRFs with stringent nitrogen (N) and phosphorus (P) limits. The volatile fatty acids fractions produced from different combinations of RAS and PS can impact the most suitable end use for each sludge type fermentation. PS resulted into higher levels of propionate, which are ideal for selecting phosphate accumulating organisms (PAO) over glycogen accumulating organisms (GAO). On the other hand, for denitrification, acetate is the preferred substrate, which was most abundant with RAS only fermentation. Our research outcomes will be of value to utilities aiming to integrate the stringent effluent nutrient (N and P) discharge targets with energy and resource recovery.